Marketing Strategy of China Heavy Duty VGV Based on 4P Theory - Xiao, Mingna; Bi, Chuanchen (Technium Social Sciences Journal, 2023)
China National Heavy Duty Truck (CNHTC) is a famous brand in China. China National Heavy Duty Truck (CNHTC) is a well-known domestic automobile brand, which occupies a certain market share in the automobile market and is recognized and supported by many consumers. However, China National Heavy Duty Truck Corporation (CNHTC) mainly focuses on heavy-duty truck products, and the development of its VGV light-duty vehicle has not been very good in the past decade, which needs to readjust its marketing strategy. This study takes China National Heavy Duty Truck Corporation (CNHTC) VGV as the research object, and explores its marketing market environment, competitive environment, etc., to find out the current marketing status of the company, and the dilemmas that appear in marketing: slow product updating, solidified brand image, lack of effective supervision and flexibility in price positioning, lack of on-line channels, inadequate management of dealers, single means of promotion, and lack of innovation in advertisement. Targeted to put forward to speed up the product update speed, pay attention to brand building, pricing and product positioning, strengthen the effective supervision of product price, online and offline channels combined, reasonable planning product channel layout and other countermeasures.